2020
DOI: 10.12965/jer.2040400.200
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise ameliorates social isolation-induced memory impairment by enhancing silent information regulator-1 expression in rats

Abstract: The effect of treadmill exercise on the social isolation-induced memory impairment in relation with the silent information regulator-1 (SIRT-1) was investigated. The rats in the control groups lived four in the standard cages for 8 weeks. The rats in the social isolation groups lived alone in the small cages for 8 weeks. The rats in the treadmill exercise groups were subjected to run on a treadmill for 30 min once a day for 8 weeks. We used step-through avoidance test for short-term memory and Morris water maz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…High level of SIRT1 expression in the brain indicates normal functioning of synaptic plasticity and memory, suggesting that SIRT1 is essential for learning ability, memory process, and maintaining of synaptic plasticity in mice [ 23 ]. Treadmill exercise improved memory impairment by increasing SIRT1 expression [ 24 ]. Long-term moderate treadmill exercise ameliorated cognitive dysfunction by activating SIRT1 to alleviate inflammatory response in the hippocampus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…High level of SIRT1 expression in the brain indicates normal functioning of synaptic plasticity and memory, suggesting that SIRT1 is essential for learning ability, memory process, and maintaining of synaptic plasticity in mice [ 23 ]. Treadmill exercise improved memory impairment by increasing SIRT1 expression [ 24 ]. Long-term moderate treadmill exercise ameliorated cognitive dysfunction by activating SIRT1 to alleviate inflammatory response in the hippocampus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54] Of ancillary interest is evidence that treadmill exercise training in rodents induces Sirt1 expression at the mRNA and protein level in brain and various other tissues. [55][56][57][58][59][60][61][62] In the brain, the effect is mediated at least in part by lactate; the molecular biology underlying this remains obscure. 61 It is reasonable to suspect that Sirt1 induction is a key mediator of the broad-ranging neuroprotective effects of aerobic exercise training-effects documented both in rodents and via epidemiology.…”
Section: Health Promotion Via Sirtuin 1 Activationmentioning
confidence: 99%
“…Voluntary wheel running following brain inflammation inhibited proinflammatory cytokine production and apoptosis, then improved spatial learning memory [13]. Performing treadmill running improved spatial learning memory, short-term memory, and recognition memory [26][27][28]. In the current study, induction of AD was found to worsen the spatial learning memory in the Morris water maze task, whereas treadmill running improved AD-induced spatial learning memory.…”
Section: Discussionmentioning
confidence: 42%